HUBUNGAN PENGETAHUAN PERAWAT TENTANG RESIKO HEALTHCARE ASSOCIATED INFECTIONS (HAIs) TERHADAP KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI DI RUANG RAWAT INAP RSUD TANGERANG SELATAN - Ika Lusiani Sugiyono; Meylis Ceriyah Hutasoit (STIKes IMC Bintaro, 2019)
Preface Nurses understanding on the nosocomial infections preventions during providing healthcare services, or known as Healthcare Associated Infections (HAIs), are needed to improve the compliance in the use of Personal Protecting Equipment (PPE). The compliance in the use of PPE is very influential in preventing of disease transmission. The knowledge about HAIs can improve nurse’s compliance. Purpose of the study is to analyze the relevance between nurse’s knowledge on the risks of healthcare associated infections (HAIs) to the compliance in the use of personal protecting equipment at the in-patient ward of RSUD Tangerang Selatan. Methodological study that use was descriptive approach with cross-sectional design. Sampling technique was using total sampling. Number of sampling were 50 respondents and the researcher using questioner as data collection tool. Data analysis was measured using SPSS program with chi-square test where the significance level was 95% (α=0.05). Result of the study using chisquare analysis showed the relevance between nurse’s knowledge on the risks of healthcare associated infections (HAIs) to the compliance in the use of personal protecting equipment (PPE), as the p value was 0.002<0.05. Conclusion of this study, there was a relevance between nurse’s knowledge on the risks of healthcare associated infections (HAIs) to the compliance in the use of personal protecting equipment (PPE) at the in-patient ward of RSUD Tangerang Selatan. Recommedation, it is recommended for RSUD Tangerang Selatan to put more concern on the increasing knowledge of the nurses on the risks of HAIs through seminars or trainings and keep up the compliance in the use of PPE